Juventudes rurais e territorialidades - Jadejiski, Rainei Rodrigues (2024)
This study, bound to the research group (CNPq) Cultures, Partnerships and Rural Schooling and the line of research Teaching, Curriculum and Cultural Processes, of the Graduate Program in Education of the Federal University of Espírito Santo (Ufes), aims to analyze the relation between the education promoted at the State Integrated Center of Rural Education (CEIER) of Águia Branca and the territorialities produced by the rural youth graduates. Theoretically, it deepens concepts such as youth/rural youth (Castro et al. 2009; Dayrell; Carrano, 2014; Weisheimer, 2005, 2009), territories and territorialities (Haesbaert, 2004, 2007), and Rural Education (Caldart, 2002, 2009, 2012, 2021; Molina, 2015). It states youthfulness as a social construction and a way of being and standing in the world, differentiating them in urban and rural contexts. Furthermore, It argues that the territorialities produced by the rural youth reflect the interaction between young people and their territories of experience and circulation, revealing how they construct their identities and sociocultural practices regarding the territory they inhabit. Understands that Rural Education, born of social movements, assumes a pedagogical work that starts from the concrete reality, the desires, and the formative needs of the people of the field. As for the methodology, the study adopts qualitative approaches in Education (Lüdke; André, 1986) focusing on oral history (Meihy; Seawright, 2021; Portelli, 2010, 2016), specifically in the thematic oral history. Under this lens, the research analyzes, through narratives, peasant youth who studied at the CEIER of Águia Branca. The data shows that the education promoted in this center has repercussions on the territorialities produced by the rural youth, which highlights the influence of schooling on the appropriation of territories. Thus, through education, there is a process of territorialization, in which the school becomes a space for identity construction and emotional and symbolic ties that go beyond the limits of the physical/ concrete territory of the institution